2001
DOI: 10.1074/jbc.m008866200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding and Functional Properties of Betaglycan, a Co-receptor of the Transforming Growth Factor-β Superfamily

Abstract: In the present work we have functionally characterized these ligand binding regions. Similar to the wild type receptor, both regions bind TGF-␤2 with higher affinity than TGF-␤1. However, only the endoglin-related region increases the TGF-␤2 labeling of the TGF-␤ type II receptor, the so-called "TGF-␤ -presentation" function of the wild type receptor. Despite this preference, both regions as well as the wild type receptor mediate the TGF-␤2-dependent Smad2 phosphorylation, indicating that they can function ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 44 publications
8
136
1
Order By: Relevance
“…As shown in Figure 6c, reexpression of TBR2 in UMRC3 cells ( þ TBR2) results in a sevenfold increase in collagen IV type 6 mRNA levels over that of UMRC3 controls, while reintroduction of both TBR2 and TBR3 enhanced collagen IV type 6 mRNA expression 11-fold. These data are consistent with a number of published reports that indicate that expression of TBR3 is essential for full TGFb responsiveness (Blobe et al, 2001;Esparza-Lopez et al, 2001). …”
Section: Recapitulation Of Tgfb Signaling Through Reintroduction Of Tsupporting
confidence: 82%
See 1 more Smart Citation
“…As shown in Figure 6c, reexpression of TBR2 in UMRC3 cells ( þ TBR2) results in a sevenfold increase in collagen IV type 6 mRNA levels over that of UMRC3 controls, while reintroduction of both TBR2 and TBR3 enhanced collagen IV type 6 mRNA expression 11-fold. These data are consistent with a number of published reports that indicate that expression of TBR3 is essential for full TGFb responsiveness (Blobe et al, 2001;Esparza-Lopez et al, 2001). …”
Section: Recapitulation Of Tgfb Signaling Through Reintroduction Of Tsupporting
confidence: 82%
“…TBR3 is the most abundant TBR in cells and has higher affinity for TGFb2 and similar affinity for TGFb1 and TGFb3, when compared to TBR2 (Boyd and Massague, 1989). TBR3 possesses two extracellular ligand-binding domains, capable of binding TGFb independently (Esparza-Lopez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is a membrane bound proteoglycan that is expressed in most cell types and tissues, and has been shown to generate, upon ectodomain shedding, a soluble form of the receptor (Andres et al, 1989;Lopez-Casillas et al, 1991). While the membrane receptor enhances the TGFb e ects, the soluble form is a potent TGFb neutralizing agent (Esparza-Lopez et al, 2001;Vilchis-Landeros et al, 2001). In our previous studies, we have shown that expression of the extracellular domain of RIII in its soluble form (sRIII) in human breast cancer MDA-MB-231 cells can sequester endogenous TGFb isoforms and antagonize their activity.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, up to date, betaglycan stands as the only identified inhibin A receptor capable of mediating its characteristic activin antagonism (15,16). Although the glycosaminoglycan chains are not required for all of these functions (10,17), they may modulate them. It has been reported that in some cell lines the nature of the glycosaminoglycan attached to membrane betaglycan core protein may sterically prevent its association with the TGF-␤ type II receptor, turning it into an inhibitor of TGF-␤ (18).…”
mentioning
confidence: 99%